Detection of a new heterozygous germline ETV6 mutation in a case with hyperdiploid acute lymphoblastic leukemia. (9th November 2017) - Duployez, Nicolas; Abou Chahla, Wadih; Lejeune, Sophie; Marceau‐Renaut, Alice; Letizia, Guillaume; Boyer, Thomas; Geffroy, Sandrine; Peyrouze, Pauline; Grardel, Nathalie; Nelken, Brigitte; Michel, Gérard; Bertrand, Yves; et al.
Abstract: ETV6 is a target of recurrent aberrations in sporadic and familial acute lymphoblastic leukemia (ALL). Here, we report on a new pedigree with a germline ETV6 mutation in which the index patient and his father developed high hyperdiploid (HeH) ALL and polycythemia vera at age 13 and 51, respectively. The index patient achieved durable complete remission without transplantation but had persistent moderate thrombocytopenia without bleeding tendency. To determine the prevalence of ETV6 alterations in HeH‐ALL, we screened 81 unrelated subjects with HeH‐ALL by single nucleotide polymorphism array and high‐throughput sequencing for the ETV6 gene. Overall, ETV6 microdeletions and mutations were identified in 9% of cases, all of which were somatic and considered as secondary events. Apart from the index patient, no germline ETV6 aberration was identified. Finally, we reviewed the literature for ETV6 germline aberrations and predispositions to ALL.